2020
DOI: 10.1186/s12960-020-0448-3
|View full text |Cite
|
Sign up to set email alerts
|

Physician workforce in the United States of America: forecasting nationwide shortages

Abstract: Background: Physicians play a critical role in healthcare delivery. With an aging US population, population growth, and a greater insured population following the Affordable Care Act (ACA), healthcare demand is growing at an unprecedented pace. This study is to examine current and future physician job surplus/shortage trends across the United States of America from 2017 to 2030. Methods: Using projected changes in population size and age, the authors developed demand and supply models to forecast the physician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
128
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 223 publications
(158 citation statements)
references
References 13 publications
2
128
0
Order By: Relevance
“…Physician shortage is an existing problem across several states in the USA and is predicted to only increase in the near future. US trained IMGs have played an integral role in providing healthcare to the children in these areas [ 1 ]. The American Academy of Pediatrics (AAP) has concluded that due to several factors such as distribution of pediatricians in the primary care sector to cater to the needs of children in rural and medically underserved areas, the rise in the number of children with chronic health conditions, physician work hour changes along with health reform efforts implemented over time to improve healthcare access for children, there is a current shortage of pediatric medical subspecialists across several fields [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Physician shortage is an existing problem across several states in the USA and is predicted to only increase in the near future. US trained IMGs have played an integral role in providing healthcare to the children in these areas [ 1 ]. The American Academy of Pediatrics (AAP) has concluded that due to several factors such as distribution of pediatricians in the primary care sector to cater to the needs of children in rural and medically underserved areas, the rise in the number of children with chronic health conditions, physician work hour changes along with health reform efforts implemented over time to improve healthcare access for children, there is a current shortage of pediatric medical subspecialists across several fields [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both the short- and long-term effects of the COVID-19 pandemic are already leading to a paradigm shift across the health care industry [ 1 - 3 ]. The pandemic has underscored systemic health disparities, clinician shortages, and financial strain that highlight the need for new innovation [ 4 - 6 ]. As the field looks toward technology to offer accessible and cost-effective solutions, now is the time to consider how digitally informed care can provide improved outcomes while reducing access inequities for marginalized communities [ 7 - 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some degree of attention has been paid over the years to the labor markets for health care professionals, such as those for physicians, pharmacists, nurses and others who are educated and trained to play specific roles in serving our health needs [1][2][3]. As health care has become more specialized and complex, health professionals have increasingly relied on para-professional workers to support their clinical roles and provide administrative assistance.…”
Section: Introductionmentioning
confidence: 99%